Integrating Canva-supported project-based learning in disaster mitigation education - Rizqina Awaliyah; Sukma Perdana Prasetya; Fahmi Fahrudin (Harmoni Sosial: Jurnal Pendidikan IPS, 2026)
This study aims to analyze the effectiveness of the Project Based Learning (PJBL) model supported by Canva in improving visual creativity and disaster understanding among grade XI students at Ma'arif NU Solokuro High School. The research employed a quantitative approach using a quasi-experimental design with two groups: an experimental group receiving PJBL-Canva-based instruction and a control group receiving conventional learning. Data were collected using pretest-posttest instruments to measure disaster comprehension and rubrics to assess visual creativity. The findings revealed that the experimental group experienced a highly significant improvement, indicated by a Sig. value of 0.000 on the Paired Sample t-test and a greater increase in mean scores compared to the control group. In contrast, the control group did not demonstrate significant improvement, as shown by a Sig. value of 0.755. The Independent Sample t-test also confirmed a significant difference between the groups with a Sig. value of 0.000. Furthermore, ANCOVA results indicated that the learning model significantly affected posttest outcomes (F = 92.363; p < 0.05), demonstrating that PJBL integrated with Canva contributed substantially to student achievement even after controlling for initial ability. Overall, this study concludes that Canva-based PJBL is highly effective in enhancing students' visual creativity and disaster-related conceptual understanding. This learning model also supports engaging, contextual, and digital-literacy-oriented instruction. Therefore, Canva-based PJBL is recommended as an innovative learning alternative, particularly for geography or subjects requiring visual creativity and deeper conceptual mastery